Tranexamic Acid Reduces Occult Blood Loss, Blood Transfusion, and Improves Recovery of Knee Function after Total Knee Arthroplasty: A Comparative Study - Liu, Wei; Yang, Chunmei; Huang, Xiujun; Liu, Ruizhong (The Journal of Knee Surgery, 2018)
This study intends to explore the effects of tranexamic acid (TA) on occult blood loss, blood transfusion, and recovery of knee function in patients undergoing total knee arthroplasty (TKA). From October 2013 to April 2015, 224 patients undergoing TKA were enrolled in this study. These patients were randomly assigned into the control group (intravenous infusion of normal saline), 10 mg/kg TA group (intravenous infusion of 10 mg/kg TA) and 15 mg/kg TA group (intravenous infusion of 15 mg/kg TA). Compared with the control group, the 10 and 15 mg/kg TA groups were lower in postoperative blood loss, occult blood loss, blood transfusion rate, and volume. In comparison to the control group, hemoglobin levels were lower and the number of red blood cells was higher at 7 days after surgery in the 10 and 15 mg/kg TA groups. Higher fibrinogen levels and lower prothrombin time (PT), activated partial thromboplastin time, D-dimer levels, thrombin time, lower the visual analog scale/score, and circumference diameter of knee joint were observed in the 10 and 15 mg/kg TA groups compared with the control group at 7 and 14 days after surgery. At 1 and 3 months after surgery, the knee joint range of motion scores, Hospital for Special Surgery scores, and Knee Society Score were increased in 10 and 15 mg/kg TA groups in comparison to the control group. TA could reduce occult blood loss and blood transfusion rate and improve recovery of knee function in patients undergoing TKA.
Keywords: tranexamic acid; total knee arthroplasty; occult blood loss; blood transfusion rate; recovery of knee function; Hospital for Special Surgery; Knee Society Score